Lung function at twelve years of age in children born very prematurely. (24th May 2012) - Zivanovic, S; Paris, M Alcazar; Lunt, A; Lo, J; Calvert, S; Marlow, N; Peacock, J; Greenough, A
Abstract : Aim: Impaired lung function appears common amongst school children born very prematurely. In one study, 56% of such children had abnormal baseline spirometry at 11 years, but all were born at or < 25 completed weeks of gestation. Our aim was to determine if school aged children born at 26 to 28 weeks of gestation had similar impairment of lung function to those born at or < 25 weeks of gestation. Methods: Lung function was assessed at 12 years of age in 38 children, the first so far assessed in the follow-up of the randomised, neonatal study of high frequency oscillation versus conventional ventilation (UKOS). Forced expiratory volume in one second (FEV1), forced vital capacity (FVC), FEV1:FVC, residual volume (RV), transfer factor for carbon monoxide (TLCO), functional residual capacity (FRC) and response to cold air challenge (CACh) were assessed. Results were considered abnormal if >1.64 standardised residuals (SR) below expected, except RV results which were abnormal if >1.64 SR above expected. The response to the CACh was considered positive if FEV1 fell by >10% of the baseline value post challenge. Results: Fifteen children were born between 26 and 28 weeks and 23 between 23 and 25 weeks of gestation. A greater proportion of the "23-25 week" children had been oxygen dependent at 28 days (93% versus 83%, p=0.63) and at discharge (35% versus 17%, p=0.26), in this small sample the differences did not reach statistical significance, but a significantly greater proportion of the "23-25 week" children had received postnatal corticosteroids (60% versus 17%, p=0.013). Overall, the lung function results abnormal in greater than 20% of the study population were FEV1 (24%), TLCO (26%) and RV (34%); 26% of the children had a positive CACh. The two groups, however, did not differ in their weight or height at follow-up, nor in any of the lung function results. Conclusion: These preliminary results suggest children born at 26-28 weeks of gestation also suffer lung function impairment at school age and of a similar degree to those born at 23-25 weeks of gestation.